A NICER look at thermonuclear X-ray bursts from Aql X-1. Issue 2 (26th November 2021) - Güver, Tolga; Boztepe, Tuğba; Ballantyne, D R; Bostancı, Z Funda; Bult, Peter; Jaisawal, Gaurava K; Göğüş, Ersin; Strohmayer, Tod E; Altamirano, Diego; Guillot, Sebastien; Chakrabarty, Deepto
ABSTRACT: We present spectral and temporal properties of all the thermonuclear X-ray bursts observed from Aql X-1 by the Neutron Star Interior and Composition Explorer ( NICER ) between 2017 July and 2021 April. This is the first systematic investigation of a large sample of type I X-ray bursts from Aql X-1 with improved sensitivity at low energies. We detect 22 X-ray bursts including two short recurrence burst events in which the separation was only 451 s and 496 s. We perform time resolved spectroscopy of the bursts using the fixed and scaled background ( fa  method) approaches. We show that the use of a scaling factor to the pre-burst emission is the statistically preferred model in about 68 per cent of all the spectra compared to the fixed background approach. Typically the fa  values are clustered around 1–3, but can reach up to 11 in a burst where photospheric radius expansion is observed. Such fa  values indicate a very significant increase in the pre-burst emission especially at around the peak flux moments of the bursts. We show that the use of the fa  factor alters the best-fitting spectral parameters of the burst emission. Finally, we employed a reflection model instead of scaling the pre-burst emission. We show that reflection models also do fit the spectra and improve the goodness of the fits. In all cases, we see that the disc is highly ionized by the burst emission and the fraction of the reprocessed emission to the incident burst flux is typically clustered around 20 per cent.